Determinação da curva de referência das medidas funcionais e dos escores Z no coração de fetos normais por meio do ecodopplercardiograma bidimensional - Amorim, Luciane Alves Da Rocha [UNIFESP] (2019)
Introduction: Fetal heart evaluation is comprises of the anatomical and functional examination. Currently, the anatomical study of the fetal heart is well established in the routine of health professionals. However, it is still not consensual which technique is optimal to be applied when evaluating fetal heart function, despite its undeniable importance. In the current literature, there are a tendency to describe the echocardiographic measurements using Z-score equations in pediatric echocardiograms, as they demonstrate greater practicality in establishing the normality or not of the findings. In fetal cardiology, however, the reference values and the Z-score equations are still under development. The objective of this study was to determine the reference values of fetal heart functional measurements at 24 and 34 weeks of gestation and to develop Z-score equations for all measures studied. Method: A single-center, prospective, cross-sectional study with normal fetuses between 24 and 34 weeks of gestation was performed. All pregnant women underwent a comprehensive Doppler echocardiogram with anatomical and functional analysis. Measurements of left and right cardiac output, mitral and tricuspid valves flow, inferior cava vein flow and pulmonary vein flow were made. Shapiro-Wilk test and histogram evaluation were performed on all variables. Linear regression was used to check the relationship between measurements and gestational age. Results: 612 pregnant women with single and normal fetuses were included. We determined the reference values and percentiles of the assessment measures for each gestational age. The variables that were not normally distributed were submitted to logarithmic or square root transformation. It was possible to develop 10 equations of Z score, being the equations of left and right ventricles output dependent on gestational age and the others being independent on gestational age. Conclusion: The present study accumulated a large database, allowing the demonstration of reference values and percentiles, as well as the development of Z score equations to facilitate echocardiographic evaluation of the fetal heart function.